Topical Directions of Informatics In Memory of V. M. Glushkov - Sergienko, Ivan V. (Springer Optimization and Its Applications,, 2014)
This work is devoted to the late Ukrainian computer scientist V. M. Glushkov  on the 90th anniversary of his birthday. Dr. Glushkov is known for his contribution to the world computer science and technology, and this volume analyzes the ideas and paths of development of informatics formulated by him, and demonstrates their important role in constructing computer technologies of basic research in the fields of applied mathematics, theories of computer programming, and computing systems.   A significant portion of the monograph is devoted to the elucidation of new results obtained  in the field of mathematical modeling of complicated processes, creation of new methods for solving and investigating optimization problems in different statements, and development of computer technologies for investigations in the field of economy, biology, medicine, and information security in systems.   The monograph will be of particular interest to informatics specialists and experts using methods of informatics and computer technologies to investigate complicated processes of different natures and developing new information technologies. It may also be useful for both graduate students and postgraduates specializing in Computer Science.